COORDINATION COMPOUND METAL COMPOUND (International Journal of Food and Nutritional Sciences, 2022)
Inorganic, analytical, organic, environmental, and industrial chemistry all fall under the umbrella of coordination chemistry. In the area of coordination chemistry, extensive research is being conducted, and many articles are released every month. The term "coordination chemistry" is a relatively new one. Coordination compounds were in use long before they were characterised, although there is no precise date for when they first appeared in chemistry. The discovery of the orange-colored cobalt ammine compound CoCl3.6NH3 by Tassaert in France in 1798 from an ammoniacal solution of cobalt chloride (CoCl2) exposed to air was a watershed moment in coordination chemistry. The separation of this new chemical from the mixture of two previously saturated compounds puzzled scientists at the time, but it took another hundred years or more for them to explain Tassaert's finding. Many theories were proposed, the most famous of which being Christian Wilhelm Blomstran's Chain Idea, which was adopted and expanded by Sophus Mads Jorgensen to explain the characteristics of cobalt and platinum ammines, but the theory failed to explain many facts and was discarded. Alfred Werner's notion of coordination compounds and his general explanation of how they work [1] is possibly the most important conceptual contribution to inorganic chemistry, similar in both direct and indirect effect to organic chemistry's concept of the tetrahedral carbon atom. In a lengthy article [2], Alfred Werner defined the fundamentals of coordination chemistry, for which he was awarded the Nobel Prize in Chemistry in 1913, the first Nobel Prize in the branch of Inorganic Chemistry, "in recognition of his work on the linkage of atoms in molecules, by which he has thrown new light on earlier investigations and opened up new fields of research, especially in inorganic chemistry" [Werner established a comprehensive theory capable of describi Since its dissemination and general acceptance throughout the decades of 1890 and 1910, it has provided a key foundation for coordination compounds and classical chemistry. Werner's complexes captivated chemists for decades afterward, and they were crucial in the development of coordination chemistry.